Depression, Anxiety and Stress in Health Professionals in the COVID-19 Context - Garcia, Gracielle Pereira Aires; Fracarolli, Isabela Fernanda Larios; Dos Santos, Heloisa Ehmke Cardoso; de Oliveira, Samuel Andrade; Martins, Bianca Gonzalez [UNESP]; Junior, Lacir José Santin; Marziale, Maria Helena Palucci; Rocha, Fernanda Ludmilla Rossi (MDPI, 2022)
To assess the prevalence of depression, anxiety and stress symptoms in health professionals in the COVID-19 pandemic context. Method: Cross-sectional study with non-probabilistic (snow-ball) sampling method. The assessment was performed using the Depression, Anxiety, and Stress Scale (DASS-21) and the prevalence of symptoms severity was calculated by point and 95% confidence interval. The analysis of the psychometric properties of DASS-21 was performed using confirmatory factor analysis (CFA) and the following goodness of fit indices: χ2/df (chi-square ratio by degrees of freedom), Tucker–Lewis index (TLI), comparative fit index (CFI) and root mean square error of approximation (RMSEA) with a 90% confidence interval. Results: The study participants were 529 health professionals (82.4% women and 66.7% nursing professionals). CFA of the DASS-21 structural model presented adequate fit for the sample (χ2/df = 3.530; CFI = 0.979; TLI = 0.976; RMSEA = 0.069). Regarding prevalence, moderate to extremely severe symptoms of depression, anxiety and stress were found in 48.6%, 55.0% and 47.9% of the participants, respectively. Conclusion: The use of DASS-21 confirmed the validity and reliability of the data. The prevalence of depression, anxiety and stress symptoms in the participants indicated a high risk of mental illness in health professionals in the COVID-19 pandemic.
Keywords: anxiety; COVID-19; depression; health personnel; occupational health; psychological stress